Dihydroquinazolinones as adaptative C(sp3) handles in arylations and alkylations via dual catalytic C–C bond-functionalization - Lv, Xin-Yang; Abrams, Roman; Martin, Ruben (Nature communications, 2022)
C–C bond forming cross-couplings are convenient technologies for the construction of functional molecules. Consequently, there is continual interest in approaches that can render traditionally inert functionality as cross-coupling partners, included in this are ketones which are widely-available commodity chemicals and easy to install synthetic handles. Herein, we describe a dual catalytic strategy that utilizes dihydroquinazolinones derived from ketone congeners as adaptative one-electron handles for forging C( sp 3 ) architectures via α C–C cleavage with aryl and alkyl bromides. Our approach is achieved by combining the flexibility and modularity of nickel catalysis with the propensity of photoredox events for generating open-shell reaction intermediates. This method is distinguished by its wide scope and broad application profile––including chemical diversification of advanced intermediates––, providing a catalytic technique complementary to existing C( sp 3 ) cross-coupling reactions that operates within the C–C bond-functionalization arena. Although derived from feedstock chemicals and therefore in principle abundant, ketones are not widely used as cross-coupling partners in organic synthesis. Herein, the authors use ketone derivatives as one-electron handles for forging C(sp3) architectures via dual photo- and nickel catalysis.